Synthesis, characterization and photo catalytic degradation of aqueous eosin over Cr containing Ti/MCM-41 and SiO2-TiO2 catalysts using visible light - Awate, S. V.; Jacob, Nalini E.; Deshpande, Suvarna S.; Gaydhankar, T. R.; Belhekar, Anagha A. (Journal of Molecular Catalysis A - Chemical, 2005)
Two series of samples were prepared namely Cr-Ti/MCM-41 and Cr/SiO2-TiO2 keeping Si/Ti mole ratio same, with different Cr loading. The physico-chemical properties of the samples were characterized by different analytical techniques such as XRD, FTIR, TEM, low temperature N-2 sorption, and UV-vis diffused reflectance spectroscopy. The impregnated TiO2 was in anatase form. The crystallite size was determined from Scherrer equation as well as by TEM. There is a difference between the shapes of nitrogen adsorption isotherms with and without Cr-loaded Ti/MCM-41 samples. The rate of nitrogen adsorption was found to increase with decrease in Cr content at lower P/P-0 for Cr-Ti/MCM-41 samples due to the blocking of the pores with Cr. All MCM-41 samples exhibited pore sizes from 24 nm to 32 nm. UV-vis diffused reflectance spectra of all Cr-loaded samples showed red shift of their absorption edges. Photo degradation of eosin dye was studied using visible light. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Cr-Ti/MCM-41; Cr/SiO2-TiO2; eosin; photo degradation; visible light

Preparation and evaluation of cellulose acetate butyrate and poly(ethylene oxide) blend microspheres for gastroretentive floating delivery of repaglinide - Rokhade, Ajit P.; Patil, Sangamesh A.; Belhekar, Anagha A.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2007)
In this study, hollow microspheres of cellulose acetate butyrate (CAB) and poly(ethylene oxide) (PEO) were prepared by emulsion-solvent evaporation method. Repaglinide was successfully encapsulated into floating microspheres. Various formulations were prepared by varying the ratio of CAB and PEO, drug loading and concentration of poly(vinyl alcohol) (PVA) solution. Encapsulation of the drug up to 95% was achieved. The microspheres tend to float over the simulated gastric media for more than 10 h. The micromeritic properties of microspheres reveal the excellent flow and good packing properties. The % buoyancy of microspheres was found to be up to 87. SEM showed that microspheres have many pores on their surfaces. Particle size ranges from 159 to 601 mu m. DSC and X-RD revealed the amorphous dispersion in the polymer matrix. In vitro release experiments were performed in simulated gastric fluid. In vitro release studies indicated the dependence of release rate on the extent of drug loading and the amount of PEO in the microspheres; slow release was extended up to 12 h. The release data were fitted to an empirical equation to compute the diffusional exponent (n), which indicated that the release mechanism followed the non-Fickian trend. (C) 2007 Wiley Periodicals, Inc.
Keywords: cellulose acetate butyrate; Controlled release; floating drug delivery; microspheres; repaglinide

Effect of gold dispersion on the photocatalytic activity of mesoporous titania for the vapor-phase oxidation of acetone - Awate, S. V.; Belhekar, Anagha A.; Bhagwat, S. V.; Kumar, R.; Gupta, N. M. (International Journal of Photoenergy, 2008)
Mesostructured titanium dioxide photocatalyst, having uniform crystallite size (6-12 nm) and average pore diameter of similar to 4.2 nm, was synthesized by using a low-temperature nonsurfactant hydrothermal route, employing tartaric acid as a templating agent. Gold additions from 0.5 to 2wt% were incorporated, either during the hydrothermal process or by postsynthesis wet impregnation. Compared to the impregnation-prepared samples, the samples synthesized hydrothermally contained smaller-size (<= 1 nm) gold clusters occluded in the pores of the host matrix. Whereas CO(2) and H(2)O were the main reaction products in UV-assisted vapor-phase oxidation of acetone using these catalysts, C(2)H(6) and HCO(2)CH(3) were also produced for higher acetone concentrations in air. The conversion of acetone was found to increase with decrease in the size of both TiO(2) and gold particles. In situ IR spectroscopy revealed that titania and gold particles serve as independent adsorption and reaction sites for acetone and oxygen molecules. Acetone molecules adsorb exclusively at TiO(2) surface, giving rise to a strongly adsorbed (condensed) state as well as to the formation of formate- and methyl formate- type surface species. Hydroxyl groups at titania surface participate directly in these adsorption steps. Nanosize gold particles, on the other hand, were primarily responsible for the adsorption and activation of oxygen molecules. Mechanistic aspects of the photochemical processes are discussed on the basis of these observations. Copyright (C) 2008.